DARI CERAMAH KE GAMIFIKASI: EFEKTIVITAS WORDWALL DALAM MENINGKATKAN HASIL BELAJAR AKIDAH AKHLAK DI MADRASAH ALIYAH - Muhammad Abid Farkhan; Amang Fathurrohman (As-Sulthan Journal of Education, 2026)
This study aims to analyze the effect of using Wordwall learning media on the learning outcomes of Akidah Akhlak for grade XII students at MA YTI Nguling Pasuruan. The background of this research is the low learning outcomes caused by conventional teaching methods that are less interactive and do not align with the characteristics of the digital generation. This study employed a quantitative approach with a quasi-experimental method using a one-group pretest-posttest design. The population consisted of 19 students who were selected as the research sample through purposive sampling. The research instruments included a multiple-choice test of 20 questions that had passed validity and reliability tests (Cronbach's Alpha = 0.889), as well as a student perception questionnaire of 20 statements using a Likert scale. Data analysis techniques included descriptive statistics, Shapiro-Wilk normality test, Wilcoxon Signed Rank Test, and N-Gain Score analysis. The results showed that: (1) students' learning outcomes before using Wordwall were in the low category with a mean pretest score of 59.21; (2) students' learning outcomes after using Wordwall improved with a mean posttest score of 86.05, with 84.21% of students reaching the Minimum Mastery Criterion (KKM); (3) there was a significant effect of using Wordwall on Akidah Akhlak learning outcomes, as proven by the Wilcoxon test (Asymp. Sig. = 0.000 < 0.05). These results were reinforced by an average N-Gain score of 0.67 (medium category) and a student perception questionnaire score of 3.00 (high category). Abstrak : Penelitian ini bertujuan untuk menganalisis pengaruh penggunaan media pembelajaran Wordwall terhadap hasil belajar Akidah Akhlak siswa kelas XII di MA YTI Nguling Pasuruan. Latar belakang penelitian ini adalah rendahnya hasil belajar yang disebabkan oleh metode pembelajaran konvensional yang kurang interaktif dan tidak sesuai dengan karakteristik generasi digital. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian eksperimen semu desain One-Group Pretest-Posttest. Populasi penelitian berjumlah 19 siswa yang sekaligus dijadikan sebagai sampel penelitian melalui teknik purposive sampling. Instrumen penelitian berupa tes pilihan ganda sebanyak 20 soal yang telah melalui uji validitas dan reliabilitas (Cronbach's Alpha = 0,889), serta angket persepsi siswa sebanyak 20 pernyataan skala Likert. Teknik analisis data menggunakan statistik deskriptif, uji normalitas Shapiro-Wilk, uji hipotesis Wilcoxon Signed Rank Test, dan analisis N-Gain Score. Hasil penelitian menunjukkan bahwa: (1) hasil belajar siswa sebelum penggunaan media Wordwall berada pada kategori rendah dengan rata-rata nilai pretest 59,21; (2) hasil belajar siswa sesudah penggunaan media Wordwall mengalami peningkatan dengan rata-rata nilai posttest 86,05 dan 84,21% siswa telah mencapai KKM; (3) terdapat pengaruh yang signifikan dari penggunaan media Wordwall terhadap hasil belajar Akidah Akhlak, dibuktikan dengan uji Wilcoxon (Asymp. Sig. = 0,000 < 0,05). Hasil ini diperkuat oleh rata-rata N-Gain sebesar 0,67 (kategori sedang) dan skor angket persepsi siswa sebesar 3,00 (kategori tinggi).